2010
DOI: 10.2298/aci1002095m
|View full text |Cite
|
Sign up to set email alerts
|

Incidental gallbladder carcinoma in regional Clinical Centre

Abstract: The incidence of incidental gallbladder cancer in this study was 0.69%. The pT-stage is very important factor in overall survival those patients. All cases of pT2-3 incidental GBC should be considered for extended radical resection after cholecystectomy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…An additional 18 studies were identified during manual cross‐referencing, resulting in a total of 73 articles, including 232 155 patients, that were eligible for data analysis. These studies were then divided into those performed in countries with a low incidence (39) 6,18–55 and countries with a high incidence (34) 7,56–88 of GBC. Characteristics of all included studies are presented in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional 18 studies were identified during manual cross‐referencing, resulting in a total of 73 articles, including 232 155 patients, that were eligible for data analysis. These studies were then divided into those performed in countries with a low incidence (39) 6,18–55 and countries with a high incidence (34) 7,56–88 of GBC. Characteristics of all included studies are presented in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…54-71) years, and 173 patients (73⋅6 per cent) were women. Nineteen studies 6,7,18,[21][22][23][24]26,36,37,41,43,44,53,59,60,67,69,75 (68 144 patients) including 178 patients with truly incidental GBC reported the clinical consequences of this diagnosis. The consequences for two patients with gallbladder metastases were not described 6,18 .…”
Section: Clinical Consequences Of Truly Incidental Gallbladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 1, There are numerous reports of the incidental gallbladder carcinoma detected after laparoscopic cholecystectomy with postoperative port-site metastasis. [6][7][8][9] Maker et al 10 in their study which included 113 patients have found that the incidence of port-site metastases after LC for GBCA is up to 40%. However, there is no consensus regarding the patophysiological mechanisms of metastases.…”
Section: Discusionmentioning
confidence: 99%
“…The Incidence of Incidental Gall Bladder Carcinoma is Different in Different Regions of the world Depending on Ethnicity and Geographic Diversity[10][11][12][13][14][15][16][17][18][19][20] …”
mentioning
confidence: 99%